ISOLASI BAKTERIOFAG SPESIFIK Pseudomonas sp. DA1 DARI BIOFILM PADA SISTEM PENGISIAN AIR MINUM ISI ULANG. - Zikra Hayati; Siti Nur Jannah; Agung Suprihadi (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
The social demand for drinking water increases both in urban and rural areas. The state encourages the development of Industrial Water Supply Depot (DAM) refills. problems occurred is no standard method for treating drinking water is sterileand lack of government supervision. This raises the issue of sanitation that is the presence of pathogenic bacteria that form biofilms in drinking water refill system. One of the bacterial pathogen is Pseudomonas. Bacteria Pseudomonas at refill drinking water can cause infections in the digestive tract. This study aims to find specific bacteriophage isolates of biofilm samples to infect bacteria Pseudomonas sp. on refill drinking water system. Isolation host Pseudomonas done in 2 ways dilution and filtration and grown on selective media Pseudomonas Isolation Agar. Isolates obtained were then characterized by gram staining and Kligler Iron Agar (KIA) test. Isolation of bacteriophages of biofilm done by bacteriophage amplification and filtration to obtain filtrate bacteriophage I and II. Test performed by using the host's infection Pseudomonas sp. DA1, Pseudomonas aeruginosa and Salmonella sp. (LIPI’s collection). The results showed that the drinking water refill depot contained positive isolates of Pseudomonas is Pseudomonas sp. DA1 and obtained isolate specific bakteriofag that can infect Pseudomonas sp. DA1. Bacteriophage titer calculation results on each sample at 3,0 x 105 PFU/ml in drinking water depot, 3,3 x 107 PFU/ml in the water product, and 9 x 107 PFU/ml water sources. Keyword: refill drinking water systems, biofilms, Pseudomonas sp DA1, bacteriophage